PERILAKU HIDUP BERSIH DAN SEHAT PEDAGANG MAKANAN DI KAWASAN UNIVERSITAS PAKUAN - Rita istiana; Muhammad Taufik Awaludin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2017)
The purposeof this study is to assess and analyze the correlation between education level, income with Behavior Clean and Healthy Food Region Traders Pakuan University. The study was conducted at the food vendors in the surrounding area Pakuan University in 2016 with a sample of 40 vendors were taken by purposive sampling. Retrieval of the data used by distributing questionnaires and direct observation interviews. Instrument calibration is done using expert judgment. Data were analyzed using statistical test of correlation and linear regression, hypothesis testing was done on a significant level of 0.01 with SPSS 20. Results showed that: 1) positive and significant correlation between education and behavior of clean and healthy food traders in the region Unpak with correlation coefficients (ry1) of 0.778, and the coefficient of determination (r2y1) of 0.606 with a regression equation Y = 0.222 + 0.746 X1. 2) positive and significant correlation between income with hygienic behavior and healthy food traders in the region Unpak with correlation coefficients (ry2) of 0.672 and a coefficient of determination (r2y2) amounted to 0.032 with the regression equation Y = 102.599 + 0.154 X2. The conclusion of this study is that the behavior of clean and healthy living can be improved by improving education and income food traders in the region Pakuan University Bogor.Keywords: Education, Income, Clean and Healthy Behavior